Does the labor-income process contain a unit root? Evidence from individual-specific time series - Magnus Gustavsson; Pär Österholm (Uppsala University, Department of Economics, 2010)
Employing econometric methods for univariate time series, this paper investigates the empirical validity of assuming a unit root in individuals' labor-income processes. Using a Swedish register-based longitudinal dataset which allows us to follow a cohort of workers from 1968 to 2005, we are able to obtain distributions of median unbiased estimates of local-to-unity parameters. The results indicate that earnings for the representative worker are governed by a process where shocks to earnings have fairly high persistence but are both economically and statistically significantly different from having permanent effects; that is, the largest autoregressive root is less than unity. These results add to the studies that question the heavy use of unit-root processes for earnings in calibrations of life-cycle models.
urn:nbn:se:uu:diva-136384
Keywords: C22; C23; J31; 330; Idiosyncratic income risk; Unit-root model; Earnings dynamics; Local-to-unity parameter; Unit Root Test; Zeitreihenanalyse; Lebenseinkommen; Kohortenanalyse; Schweden